The Impact of Patient-Centered Care on the Patient Experience in Healthcare Settings - Shadi Ahmed Alghamdi,; Abdulwahab Abdullah Y. Ahmed,; Saleh Husain Al Abbas,; Mohammed Alhassan Hassan Alsubaihi,; Fatimah Ali Mohammad Alshaery,; Essa Aaliy Almutiry,; Ziyad Abdulrahman Mubarak Alosfur,; Manal Hassan Medaeen Aljohani,; Layla Husseain Abduaziz Zainaldeen,; Ahmed Mohammed Abdullah, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Patient-centered care refers to the process of empowering patients and centering care around a patient's preferences, values, and goals. Empowering patients means that they are educated about their medical condition and treatment plan, as well as being encouraged to be active in their care processes. Patient-centered care has been shown to contribute to favorable patient outcomes in terms of treatment adherence, patient satisfaction, treatment outcomes, and overall patient experience with a variety of medical conditions. The purpose of this review is to explore the patient experience with exposure to the medical home model—a model shown to improve the delivery of patient-centered care. The patient experience and general scores of quality of care are fairly consistent across payers and diagnoses. Improving the quality of care within our population has been a goal of most nations for a long time. Various remote and rural communities are often more at risk when it comes to receiving the high-quality, patient-centered care that aligns with the patient-centered medical home model design principles than those in urban areas. Patient-centered care was proposed in response to the increasing complexity and specialization of health care and the increasing number of patients. These changes highlight the need for relationship, trust, and respect between the doctor and the patient as essential features of patient-centered care. Given the relative simplicity, there is enormous potential to develop solutions to improve the experience of care for more remote and rural patients in line with the principles of the patient-centered medical home model. That is our focus in the present situation.